Pendampingan Pemanfaatan Media Sosial dalam Meningkatkan Branding Pada UMKM Toko Olahraga Menang Jaya Putra - Itayudasari, Margareta; Sia, Tandian Prillia Irianti; Saputra, Gabriel Kevin; Dior, Grand; Sugiarto, Agus (LPPM Universitas Timor, 2025)
Small and medium enterprises (SMEs) are an important sector in the country's economy. Thus, SMEs need to get support for their development. This community service activity aims to provide training and assistance to MSMEs at Menang Jaya Putra Sports Stores in utilizing digital marketing as a marketing strategy to reach more markets and strengthen the branding of Menang Jaya Putra Sports Stores. In this case, through the use of social media, namely Instagram and websites. The series of community service activities in creating Instagram and websites starts from the observation, planning, implementation and evaluation stages. The result of this community service activity is that MSME partners become more knowledgeable and understand how to manage Instagram and websites so that they can participate in the important role of digital marketing.